The Application of ta'awun concept on takaful in Malaysia - Asma', Ahmad Puad Halmi (2017)
This research aimed to investigate the application of ta'awun concept in takaful and its relation to the takaful model in Malaysia. Based on three main objectives, this research reviewed three main takaful models that have implemented the ta 'awun concept in rnudharabah, wakalah and hybrid takaful model. For the first objective, this research examined the meaning of ta 'awun concept. Secondly, this research explored the application of ta 'awun concept in takaful. Thirdly, this paper comes out with the issues of ta 'awun in takaful as well as the recommendations that can be adopted by takaful operators to overcome these issues. At the end of this paper, researcher concluded that the pure ta 'awun concept is still yet to be achieved. However, the researcher also did not reject the possibility that the takaful model will be changed in the future operation. Hence, to make sure all the objectives that been listed are answered progressively, the most suitable method that can used is qualitative research methodology. This research integrated the source of relevant literatures and the interviews. In the future, this research can be expanded whether these issues that arise in this takaful industries may be benefited using the new model of cooperative takaful